Laughing Out Loud: How Humor Shapes Innovation Processes Within and Across Organizations - Bogers, Marcel; Brem, Alexander; Heinemann, Trine; Tavella, Elena (Not All Claps and Cheers - Humor in Business and Society Relationships, 2018)
Innovation processes increasingly rely on the collaboration between different stakeholders across various boundaries, including functional, hierarchical and organizational boundaries. Such boundary-crossing interactions can rely on different types of mechanisms, activities and boundary objects. Humor might act as an appropriate managerial tool to shape such interactions as it affects the social positions of and relationships between individuals. In this article, we present a case study of how humor is employed at the micro-level of collaborative innovation processes. Based on data from workshops in which participants work together to construct new business models for a particular company, we employ the method of conversation analysis to find that humor (laughter in particular) can be an important condition for the acceptance of proposals at the interactional micro-level of innovation processes. A key finding is that company-internal representatives’ use of humor differs from company-external participants in terms of their orientation to having different rights and responsibilities in the innovation process
CRIS-Team WoS Importer:2019-08-02
Keywords: humor; laughter; business models; open innovation; conversation analysis